Gogol's eloquentia corporis Einverleibung, Identifikation und die Grenzen der Figuration - Drubek-Meyer, Natascha (Slavistische Beitraege, 1998)
With regard to Gogol, the eloquentia corporis should be understood in the double sense of the word. First in the original, as described above, with the help of rhetoric, based on the actio- and pronunciatio teachings (see below), and then literally: as eloquence of the body, both as an independent staging of physical behavior and in its impact on the body Text.